Analisis Komparatif Parameter Radio Jaringan 4G LTE pada Kondisi Idle dan Dedicated Berdasarkan Data Drive Test - Ranik Jintan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Long Term Evolution (LTE) is a fourth-generation cellular network technology that requires periodic service quality evaluation to maintain network performance. One common evaluation method is drive testing, which can be conducted under two different Radio Resource Control (RRC) states, namely dedicated mode (RRC Connected) and idle mode (RRC Idle). This study aims to analyze and compare the radio parameters of SINR, RSRP, Serving Cell RSRQ, CQI, PDSCH modulation, and Physical Resource Block (PRB) allocation between these two conditions. Data were obtained through drive testing using a TEMS Pocket device in Padang City and processed using TEMS Discovery, with 1,070 samples in dedicated mode and 1,006 samples in idle mode. The analysis was conducted using descriptive statistics in the form of mean values and the percentage of samples meeting Key Performance Indicator (KPI) thresholds. The results show that RS SINR and RSRQ were slightly better in idle mode (9.26 dB and -10.85 dB) than in dedicated mode (8.45 dB and -11.40 dB), while RSRP was better in dedicated mode (-84.36 dBm versus -86.22 dBm). The most significant difference was found in modulation, with 64QAM dominating in dedicated mode (47.18%) and QPSK dominating in idle mode (89.15%), as well as in PRB allocation, which remained constant at a minimum of 4% in idle mode but varied dynamically between 4% and 68% in dedicated mode. These findings indicate that the UE's RRC state significantly affects the scheduling mechanism, modulation selection, and resource allocation in LTE networks.